Effect of Habit and Car Access on Student Behavior Using Cars for Traveling to Campus. (2015) - Setiawan, Rudy; Santosa, Wimpy; Sjafruddin, Ade
Abstract: This study reports an investigation of psychological factors influencing this behavior from the perspective of the Theory of Planned Behavior and Norm Activation Model, with the addition of habit and car access. Students from three different university campuses in Surabaya, Indonesia, (n = 312) completed a survey on their car commuting behavior. Results indicated that habit and ascription of responsibility were the strongest factors that influence personal norm, perceived behavioral control and personal norm were the strongest factors that influence behavioral intention, and habit was the strongest factors that influence actual behavior, while car access only significantly influence habit, rather than both perceived behavioral control and actual behavior. Habit, awareness of consequences, and ascription of responsibility explain 54% variance of personal norm. Attitude, subjective norm, perceived behavioral control, and personal norm explain 50% variance of the behavioral intention. In turn, behavioral intention, habit, and car access explains 55% of the variance of the actual car use. Implications of these findings are that in order to alter the use of car, university should implement both structural and psychological interventions. Effective interventions should be designed to raise students' awareness of consequences and sense of responsibility of negative aspects of car use.